A Project-Based Assessment Model of English for Senior High School Grade X - Levyn Gracia Hanardi (Indonesian Journal of English Language Studies (IJELS), 2015)
Related to the implementation of the Curriculum 2013, project-based learning becomes one of the learning models that should be implemented in teaching and learning activities. Hence, outcome-based assessment and authentic assessment are considered appropriate model for project-based learning because they are based on activities that represent a real-life setting. The purpose of this article is to develop an alternative model of project-based assessments that are related to the implementation of the Curriculum 2013. This model is related to the basic competences and objective of the lesson unit. Designed from concepts of project-based learning, authentic assessmemnt and outcome-based assessment, this project-based assessment model can be one example of improvement of life quality in English language learning. It is hoped that the project-based assessment model will improve a better understanding of the needs of students because it offers students‘ opportunity to investigate and discover authentic topics of interest. Using this model of project-based assessment, students‘ engagement in learning process can be improved.